THE EVOLUTION OF THE MAQĀṢID AL-SHARĪ‘AH PARADIGM: FROM A CONCEPT IN USHUL AL-FIQH TO A METHODOLOGICAL APPROACH IN ISLAMIC LAW - Imam Kamaluddin; Amir Sahidin; Setiawan bin Lahuri; Mohammad Muslih (Universitas Nurul Jadid, 2026)
Maqāṣid al-sharī‘ah has not only been understood as a normative concept within ushul al-fiqh, but has also undergone a paradigmatic evolution into a methodological approach for addressing contemporary legal and social issues. This article aims to examine the evolution of the maqāṣid al-sharī‘ah paradigm from both historical and systematic perspectives, beginning with its conceptual roots in the classical tradition of ushul al-fiqh, its emergence as an independent scholarly discipline, and its subsequent transformation into a methodological framework in the development of modern Islamic law. This study employed a qualitative method using a library research approach, drawing upon primary and secondary sources from both classical and contemporary literature. Data analysis was conducted through descriptive-analytical, historical, and conceptual methods. The findings indicate that maqāṣid al-sharī‘ah has developed gradually, reaching its peak of systematic formulation in the thought of Imam al-Shatibi, and later expanding significantly in the modern era through the contributions of contemporary scholars. The paradigmatic evolution of maqāṣid al-sharī‘ah has proceeded through four principal stages: its implicit presence in scriptural texts (nusūs) and in the understanding of the early Muslim generations (al-salaf); its integration into the studies of fiqh and ushul al-fiqh; its establishment as an independent scholarly discipline; and its application as an approach to addressing various contemporary issues. The conclusion of this article affirms that the transformation of maqāṣid al-sharī‘ah from a concept within ushul al-fiqh into a methodological approach strengthens its relevance as an instrument for the renewal of Islamic law, making it responsive to contemporary challenges.